Learning System in Salafi Manhaj Boarding School - Fitri Meliani; Hasan Basri; Andewi Suhartini (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This article explains the development of Islamic education in Indonesia. The focus of the discussion was the Salafist boarding school. This article aims to find a form of Islamic education that develops in Islamic boarding schools with Salafi ideology (manhaj Salafi). This study uses the literature method. This article concludes that Salafist Islamic boarding schools are a new model of Islamic education in Indonesia today. This pesantren model is different from pesantren in general which has long been developed in Indonesia. The triggering factor for its development is the influence of global Islamic currents, and provides variations in Islamic education patterns, especially at Pesantren institution in Indonesia. The curriculum used at the Assunah Islamic Boarding School both in formal and non-formal education is indicated by radicalism as it is known by the public regarding the Salafist community, but it is more directed towards Salafus Saleh, namely following religious behavior based on the Qur'an, Sunah Rasul and the practice of the life of the previous pious (generation of Friends). The materials taught at the Assunah Islamic Boarding School, it has an impact on the Aqidah and Morals of students, where students or the community who diligently follow an education at the Assunnah Islamic Boarding School have strong aqidah, have polite behavior, tawad'u, have a high social spirit and are sincere.